Correlation between expert model evaluation and competitive successfulness of young categories in Alpine skiing - Lešnik, B.; Pavlovic, L.; Pišot, R.; Žvan, M. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
Expert modelling has been represented as an important part of planning and conducting training and analysing the effects of training of different categories of competitors in Alpine skiing in Slovenia. On the basis of a heuristic approach, a model of successfulness was formed. In the category of older boys (U16), the model consists of 17 dimensions of a motor subsystem and of 8 dimensions of a morphological subsystem; on the other hand the competitive successfulness (criterion variable) is assessed on the basis of the calculation of the points won in the Rauch Cup competitions in the 2015/16 season. Motor and morphological dimensions were measured on the sample of 31 active competitors in the category of older boys (U16). With the help of the SMMS program package, marks were calculated at all levels of a potential model of successfulness. Marks calculated for an individual competitor as well as for the whole group serve the coaches as a useful orientation when planning and conducting the training process. In the second part of the survey, we intended to establish the connection between the marks calculated by means of the expert system method (heuristic approach) and the criterion variable. The calculated Pearson`s correlation coefficient confirmed the statistically significant connection between the calculated marks (expert system method) and the actual successfulness (points won in the Rauch Cup competitions). The result obtained (r=0.47) is a relevant indicator of the validity and appropriate configuration of a reduced model of potential successfulness.